1991
DOI: 10.3181/00379727-197-43225
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroandrographolide Succinic Acid Monoester as an Inhibitor against the Human Immunodeficiency Virus

Abstract: Dehydroandrographolide succinic acid monoester (DASM) is the dehydroandrographolyl ester of succinic acid; and andrographolide, from which DASM is made, is the major diterpenoid lactone found in the Chinese medicinal herb, Andrographis paniculata. DASM has been found to be an inhibitor against the human immunodeficiency virus (HIV) in vitro. It was nontoxic to the H9 cell at the concentrations of 50-200 (average, 108) micrograms/ml and was inhibitory to the HIV-1 (IIIB) at the minimal concentration of 1.6-3.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 10 publications
0
61
1
Order By: Relevance
“…Seubsasana et al showed that andrographolide exhibits antireplication activity and decreases the expression of gpC and gpD throughout treatment, although it was able to inhibit HSV entry by less than 50 % [32]. Chang et al [33] found that andrographolide cannot directly inhibit viruses, but inhibits virusinduced cell signaling dysregulation, which results in an increase in CD4 + lymphocytes [33].…”
Section: Discussionmentioning
confidence: 99%
“…Seubsasana et al showed that andrographolide exhibits antireplication activity and decreases the expression of gpC and gpD throughout treatment, although it was able to inhibit HSV entry by less than 50 % [32]. Chang et al [33] found that andrographolide cannot directly inhibit viruses, but inhibits virusinduced cell signaling dysregulation, which results in an increase in CD4 + lymphocytes [33].…”
Section: Discussionmentioning
confidence: 99%
“…The present study revealed that SEA inhibits the cleavage of Q-HA HKV by furin ( Figure 5) and also by PC5 and PC7 (results not shown). Furthermore, SEA exhibits antiviral properties against HIV-1 and HIV-2 in H9 cells at concentrations in the low micromolar range [49], which is the range observed from the in itro processing of Q-HA HKV by furin. Thus future studies aimed at improving the inhibitory and cell-permeability properties of SEA might be very beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…43) Furthermore, andrographolide has been reported to possess an inhibitory effect on HIV replication and interference with HIV-induced cell fusion. [40][41][42] Andrographolide promoted interferon (IFN)-α, IFN-γ, tumor necrosis factor (TNF)-α inductions of peripheral blood mononuclear cells (PBMCs), enhanced phagocytosis activity of peritoneal macrophage from guinea pig to phagocytosis cock erythrocyte, as well as augmented the cytotoxicity mediated by natural killer cells from PBMCs to damage the K562 cell lines. These observations suggested andrographolide as an immunostimulant agent which could modulate both antigen specific and nonspecific immune function by means of its natural killer cells and macrophage and cytokines induction.…”
Section: Immunological Potentialmentioning
confidence: 99%
“…5) In Thailand, this plant was selected by the Ministry of Public Health as one of the medicinal plants to be included in "The National List of Essential Drugs A.D. 1999" (List of Herbal Medicinal Products). 6) Extensive research has revealed that Andrographis paniculata has a surprisingly broad range of pharmacological effects and some of them are extremely beneficial, such as antiinflammatory, [7][8][9][10][11] antidiarrhoeal, 12,13) antiviral, 14) anti-malarial, 15,16) hepatoprotective, [17][18][19][20][21][22][23][24][25][26][27][28][29] cardiovascular, 30,31) anticancer, [32][33][34][35][36][37][38][39] and immunostimulatory [40][41][42][43][44] activities. On the other hand, male reproductive toxicity 45) and cytotoxicity 46) of this plant have been reported as well.…”
Section: Introductionmentioning
confidence: 99%